Reading Experiences of Nonnative-English-Speaking Students Majoring in English Language Teaching: Pengalaman Membaca Siswa Non-Bahasa Inggris Jurusan Pengajaran Bahasa Inggris - Hartatik, Sri Fatmaning; Lestari, Hernina Dewi (Universitas Muhammadiyah Sidoarjo, 2016)
This study attempts to synthesize the findings of an Indonesian case study on reading experiences of nonnative-English-speaking ELT students. The researchers examined 36 students of bachelor program students using a descriptive qualitative design. The finding revealed that 55.6% of the students spent 2-3 hours reading, 27.7% spent 1-2 hours reading, while the rest 16.7% spent less than an hour reading. In term of genre, 69.4% of the students preferred scientific reading genre while 30.6% preferred fiction. Regarding the mode of reading materials, 86.1% of the students used printed material and the other 13.9% used digital reading material. The finding of this study presented that 75% of the students liked to read materials in their first language while the rest 25% preferred to read reading materials in English. About the students’ preference of reading activities, the data showed that 63.89% of the students chose activities such as a combination of doing preview, giving keywords, scanning, skimming, giving clarification, asking and answering questions, and making conclusions while 36.11% preferred reading activities involving a combination of brainstorming, conducting survey, reciprocal teaching, doing evaluation, making inference, re-reading, thinking aloud, and having discussion as the reading activities. In term of the place to read, 50% of the students read at home, 27.8% read in the classroom, and 22.2% read at the library. About the reading experience, 63.89% of students were satisfied while the other 36.11% thought that their reading experience was insufficient.